Analisis Hukum Prinsip Bagi Hasil dan Resiko dalam Kegiatan Penghimpunan Dana di Perbankan Syariah - Fatahullah - (Jatiswara, 2012)
One of the activities of Islamic banking business is accumulating funds from the public by using wadi’ah and mudarabah contract muthlaqah. Contract wadi'ah developed in Islamic Banking is wadi'ah clearing and savings wadi'ah, while Mudharbah muthlaqah principle is applied by Islamic banks in the form of savings and deposits mudarabah. From the second contract mudharabah only be done while sharing agreement wadi’ah but it should not be giving bonuses to customers but on the willingness and may not be agreed upon beforehand. While the main principles of Islamic banking operations is an agreement to the yield and risk, where banks and customers share the profits based on the ratio of the outcome is predetermined in the contract. The risk is to assume liability for any damages caused by events beyond the fault of either party. There are several types of risk in the Islamic banking financing risk, market risk and operational risk. A key feature of the results is that the gains and losses on the responsibility shared by both lenders and by employers. Method of sharing in Islamic banking are two of profit sharing and revenue sharing, the method should be stated in the agreement made ​​at the beginning of the agreement. The choice of method for determining the outcome so the gains customers and banks. Besides, it is possible for the goal should also be determined by the amount of profits that fund management do Islamic banking, ie, the greater the profit, the greater the bank to reverse the result if a small profit then the results have to be small.